Recommendation of Suitable Loading Waveforms and Wavelength Equations for Dynamic Modulus Based on Measured Wheel Loads - Xiongwei Dai; Xiaodi Hu; Ying Gao (Advances in Materials Science and Engineering)
Dynamic modulus is a key parameter in the pavement structure design and analysis. A haversine loading waveform is the most widely recommended waveform in the laboratory to obtain the dynamic modulus of asphalt mixtures by test protocols, which may not completely represent all field loading conditions. The aim of this study is to investigate the suitable vertical compressive stress pulse waveforms at different depths under different pavement structures and to obtain the best fitting waveforms by using the least squares method. Specifically, the vertical compressive stress of different pavement structures was calculated by utilizing a three-dimensional finite element program incorporating with the measured wheel loads. The results revealed that the vertical stress pulse waveforms at different depths in asphalt layer were different within different pavement structure combinations. Generally, the square waveform fitted the vertical stress pulse waveform better for the shallow depth of the surface layer. The haversine waveform became more suitable while the depth increased. The bell waveform was better when the depth went deeper (i.e., 10 cm). In addition, the method of choosing waveforms at different depths of different pavement structures was provided, and the equation of calculating wavelength was recommended. Moreover, dynamic modulus under different loading waveforms were analysed through laboratory test, and the process for obtaining dynamic modulus of asphalt layer in any depth was presented.